(untitled) (ҚазҰУ Хабаршысы. Биология сериясы, 2018)
Lung cancer is one of the most common malignant diseases. It is expected to involve more than 200 candidate genes in the development of the non-small cell lung cancer (NSCLC). The present study aimed to study the interaction characteristics of the 137 NSCLC candidate genes and miRNAs. The data obtained show that a significant number of genes are targets of two or more mRNAs. The mRNA of some genes contain binding sites for several miRNAs with overlapping nucleotide sequences, which have been termed clusters. The properties of clusters of non-small cell lung cancer genes, containing binding sites of several miRNAs, were studied for the first time. The properties of clusters with a large number of miRNA binding sites in the 5’UTR are considered. The mRNA of CHKA, E2F1, HMGA2, PTEN, HTRA2, ING1, MTA3, SMARCA4, NFATC2 genes contain clusters of binding sites for the largest number of miRNAs. Several clusters are available in the CDS mRNA of CEBPA, NOTCH3, TRIO, LATS2, RB1 and ZBTB7A genes. 32 genes are targets of 49 miRNAs, binding sites of which are localized in the 3’UTR. The CDK6 and IRS1 genes have clusters with the largest number of miRNA binding sites. The AKT1, EMP and HMGA2 genes have clusters of 34 nt, 40 nt and 41 nt in length, respectively, of the binding sites of three miRNAs. Each mRNA of BCAR1, ITGA11, MYLK, PTK6, PXN, SOX2 and SSX2 genes has clusters of the binding sites of two miRNAs. It is assumed that the expression of the examined genes will depend more on the miRNA interacting with mRNA with a higher free binding energy. Key words: miRNA, mRNA, Non-Small Cell Lung Cancer, target genes.